Factors affecting consumers' behavioral intention towards apparel stores: A test of the mediating role of brand satisfaction - (:unkn) unknown (Lukasiewicz Research Network - Institute of Biopolymers and Chemical Fibres, 2013)
The research studied the factors that affect consumers' behavioral intention towards apparel stores. Three different aspects of behavioral intention were examined: consumers' purchase intention (PI), willingness to pay more (WPAY), and brand recommendation (RECM). Specifically the authors propose a model in which consumer satisfaction with the store brand mediates the effects of attitude towards sales personnel and the convenience of the store's payment conditions or options on PI, WPAY, and RECM. The relationships hypothesized in the model were tested using two apparel store brands familiar to consumers in the city of Istanbul, Turkey. All findings were in favor of the model proposed for both apparel store brands studied, which were either a sample of men or women.
Keywords: Attitude towards sales personnel; Payment conditions; Purchase intention; Recommendation; Satisfaction; Willingness to pay more